2012
DOI: 10.1016/j.margeo.2012.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Shallow stratigraphic control on pockmark distribution in north temperate estuaries

Abstract: Pockmark fields occur throughout northern North American temperate estuaries despite the absence of extensive thermogenic hydrocarbon deposits typically associated with pockmarks. In such settings, the origins of the gas and triggering mechanism(s) responsible for pockmark formation are not obvious. Nor is it known why pockmarks proliferate in this region but do not occur south of the glacial terminus in eastern North America. This paper tests two hypotheses addressing these knowledge gaps: 1) the region's uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 41 publications
2
29
0
3
Order By: Relevance
“…Indeed, the role of sedimentation rate in pockmark morphology has been revealed in Belfast Bay where Brothers et al . [] found that the largest pockmarks occur where Holocene sediment is thickest. Seismicity and faulting can cause an overpressure to initiate gas seeps but, as presented previously, the study area is relatively stable, not disturbed by faults, and shows very low seismic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the role of sedimentation rate in pockmark morphology has been revealed in Belfast Bay where Brothers et al . [] found that the largest pockmarks occur where Holocene sediment is thickest. Seismicity and faulting can cause an overpressure to initiate gas seeps but, as presented previously, the study area is relatively stable, not disturbed by faults, and shows very low seismic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Microbial methanogenesis may lead to accumulation of free gas due to the soft, cohesive, low permeable sediments of the Witch Ground Basin instead of migrating out of the sediments (Boudreau et al, 2001;Boudreau et al, 2005). Such a scenario has been proposed for organic-rich sediments in the Arkona Basin, Baltic Sea, (Abegg & Anderson, 1997;Mogollón et al, 2012;Orsi et al, 1996), and Belfast Bay, Maine, USA (Brothers et al, 2012). There, pockmark formation is dependent on the sediment thickness, flux of organic matter, and sedimentation rates.…”
Section: Class 2 Pockmarks-timing and Controls Of Fluid Ventingmentioning
confidence: 99%
“…They occur in the majority of aquatic environments including lakes, deltas and estuaries (e.g. Berkson and Clay, 1973;Hovland et al 1997;Brothers et al 2012). In most reported cases of pockmarks around the globe the fluid involved is methane gas and thus they are frequently referred to as 'gas pockmarks' (Judd and Hovland, 2007).…”
Section: Introductionmentioning
confidence: 99%